2012
DOI: 10.1037/a0024781
|View full text |Cite
|
Sign up to set email alerts
|

Sleep normalization and decrease in dissociative experiences: Evaluation in an inpatient sample.

Abstract: We conducted a longitudinal study to investigate the relation between sleep experiences and dissociative symptoms in a mixed inpatient sample at a private clinic evaluated on arrival and at discharge 6 to 8 weeks later. Using hierarchical regression analyses and structural equation modeling, we found a link between sleep experiences and dissociative symptoms and determined that specifically decreases in narcoleptic experiences rather than insomnia accompany a reduction in dissociative symptoms. Although sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 53 publications
7
55
0
Order By: Relevance
“…Significant connections between sleep experiences and dissociative experiences were observed that alleviated levels of dissociative experiences were determined by decreases in narcoleptic experiences rather than insomnia. Authors concluded sleep hygiene may contribute to the treatment and prevention of dissociative psychopathology (van der Kloet, Giesbrecht, Lynn, Merckelbach, & de Zutter, 2012). Similar findings were replicated in a more recent study that heightened dissociation in response to 1-night total sleep deprivation was strongly linked to increased Dehydroepiandrosteronesulfate (DHEA-S) (correlation was r=0.80), a hormone intimately dependent on circadian regulation and implicated in neuroprotection, neuronal plasticity and excitability (Selvi, Kilic, Aydin, & Guzel Ozdemir, 2015).…”
Section: Introductionsupporting
confidence: 69%
“…Significant connections between sleep experiences and dissociative experiences were observed that alleviated levels of dissociative experiences were determined by decreases in narcoleptic experiences rather than insomnia. Authors concluded sleep hygiene may contribute to the treatment and prevention of dissociative psychopathology (van der Kloet, Giesbrecht, Lynn, Merckelbach, & de Zutter, 2012). Similar findings were replicated in a more recent study that heightened dissociation in response to 1-night total sleep deprivation was strongly linked to increased Dehydroepiandrosteronesulfate (DHEA-S) (correlation was r=0.80), a hormone intimately dependent on circadian regulation and implicated in neuroprotection, neuronal plasticity and excitability (Selvi, Kilic, Aydin, & Guzel Ozdemir, 2015).…”
Section: Introductionsupporting
confidence: 69%
“…Clinically insomniac patients score high on the Dissociative Experiences Scale with scores correlated to quantifiable EEG parameters [39]. Conversely, in a mixed psychiatric inpatient sample, an improvement in sleep quality led to a decrease in dissociative experiences [40]. Our PSG findings in patients with dissociative seizures suggest that sleep deprivation might be a common occurrence in these patients, supporting a possible contribution to the propensity for dissociative attacks.…”
Section: Discussionmentioning
confidence: 61%
“…Sleep disturbances are common symptoms of depressive and anxiety disorders, but the link with PNES may be more than simple comorbidity. Both experimental and clinical studies have suggested that sleep deprivation promotes dissociative tendencies (van der Kloet et al, 2012a), and one study on a mixed psychiatric inpatient sample has shown a decrease in dissociative symptoms after sleep normalization (van der Kloet et al, 2012b), suggesting that improvement of sleep might be of therapeutic use in patients with PNES.…”
Section: Sleep Disturbancementioning
confidence: 99%